Devastação feminina: a outra face do amor - Barbosa, Marina Silvestre (2018)
There is no limit to the concessions each woman makes to a man, Lacan (1974) stated in Television. It is possible to observe such cases in history, literature, music and psychoanalytic clinic. This has led writers, musicians and psychoanalysts to produce works on the way women love. They use various semblance to disguise the lack of a signifier that designates what it is to be a woman. Love is considered one of those semblances that can buffer the lack of the female signifier. Given this, the question of the importance of love for women is questioned, and consequently we try to identify what led Lacan (1975-1976) to affirm that the man can be a devastation for the woman. Thus, the present research aims to analyze, from the Lacanian propositions, the concept of female devastation, under the hypothesis that this can be one of the effects of the so-called female enjoyment. For that, a theoretical research was carried out in psychoanalysis. A research was carried out in the work of Jacques Lacan, mainly from Seminar XX On feminine sexuality, the limits of Love and Knowledge (Encore) (1972-1973) and also in texts of contemporary authors that discuss aspects related to devastation, feminine sexuality and female enjoyment. The theorizations about female sexuality have changed since Freud and the beginning of Lacan's teaching. With the notion that feminine sexuality is beyond the phallus, developed by Lacan in Seminar XX, it was possible to discuss the devastation in the amorous partnerships. It is concluded that female devastation can be considered the other face of love, since it is related to the fall of love as a semblant that can provide a limit to female enjoyment.